Forming Religious Character through Hizbul Wathan Guidance at Muhammadiyah 3 Elementary School Denpasar - Syamsuddin, Muhammad; Haris, Abdul; Yazid, Syamsurizal (Asian Journal of Early Childhood and Elementary Education, 2025)
This study aims to describe the formation of religious character through Hizbul Wathan scouting activities at Muhammadiyah 3 Elementary School in Denpasar. The research uses a qualitative approach with subjects consisting of the school principal, the head of student affairs, and the scout leaders. Data were collected through observation, interviews, and documentation. To test the validity of the data, the researcher used triangulation of techniques and sources. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data condensation, data presentation, and drawing conclusions. The results of the study show that the implementation of religious character formation through Hizbul Wathan scouting activities at Muhammadiyah 3 Elementary School in Denpasar was carried out in three stages: planning, implementation, and evaluation. Planning was done by designing lessons outlined in the syllabus and materials that had been prepared. The implementation stage involved integrating religious values with scouting materials. Meanwhile, the evaluation stage was carried out twice at the end of each semester, covering observations, attendance, student comprehension of the material, and the SKT (Standard Knowledge Test). The results of the evaluation of the Hizbul Wathan extracurricular activities were then recorded in the students' report cards.